Exploring the ecological and evolutionary relationships between Rickettsia and hard ticks in the Neotropical region - Estrada-Peña, Agustín (2021)
This study addresses a meta-analysis of the distribution of Rickettsia spp. in the Neotropical region, as well as their associations with ticks and vertebrates. A total of 219 published reports on Rickettsia in ticks in the target region were compiled, providing 599 records of 31 species of Rickettsia recorded in 50 species of Ixodidae. The aim is to capture the phylogenetic relationships between rickettsiae and the ticks carrying them in the target region, with a focus on the co-speciation ticks-rickettsiae. We compared the phylogeny of ticks, the records of rickettsiae, the environmental gradients colonized by ticks and the effect of the phylogenetic composition of vertebrates feeding ticks on the detection of Rickettsia in ticks. Results show that differences in rickettsial composition in ticks do not depend on the vertebrate's blood-source. This is the first time this result is demonstrated. This study pinpoints that some Neotropical rickettsial organisms are associated with well-defined phylogenetical clusters of ticks. Secondarily, and probably only in a few cases, rickettsiae share species of phylogenetically distant ticks distributed along a gradient of environmental traits in which the ticks overlap (i.e., the different strains of Rickettsia parkeri sensu lato). We outline the importance of some ticks that share hosts and habitat: these ticks may act as “bridges” for the circulation of rickettsial species. There are also many species of Rickettsia that have been detected so far in only one tick species, pointing to a tight relationship or to the lack of data preventing conclusions about the detection of these bacteria in other ticks. Two species, namely Rickettsia amblyommatis and Rickettsia bellii have been recorded in the majority of ticks in the region (mainly Amblyomma spp.) and seem to be not associated with definite tick species because they may be an essential symbiont of the ticks. We conclude that an adequate analysis of rickettsiae-ticks-habitat is necessary to address the human health issues derived from the infections by rickettsiae.